Adeno Associated Viral Vector Delivered RNAi for Gene Therapy of SOD1 Amyotrophic Lateral Sclerosis - Stoica, Lorelei; Sena-Esteves, Miguel (Frontiers in Molecular Neuroscience, 2016)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease caused by progressive loss of upper and lower motor neurons. Mutations in superoxide dismutase (SOD1) are a leading cause of ALS, responsible for up to twenty percent of familial cases. Although the exact mechanism by which mutant SOD1 causes disease remains unknown, multiple studies have shown that reduction of the mutant species leads to delayed disease onset and extension of lifespan of animal models. This makes SOD1 an ideal target for gene therapy coupling adeno associated virus vector (AAV) gene delivery with RNAi molecules. In this review we summarize the studies done thus far attempting to decrease SOD1 gene expression, using AAV vectors as delivery tools, and RNAi as therapeutic molecules. Current hurdles to be overcome, such as the need for widespread gene delivery through the entire central nervous system, are discussed. Continued efforts to improve current AAV delivery methods and capsids will accelerate the application of these therapeutics to the clinic.